VisionMD: an open-source tool for video-based analysis of motor function in movement disorders - Gabriela Acevedo; Florian Lange; Carolina Calonge; Robert Peach; Joshua K. Wong; Diego L. Guarin (npj Parkinson's Disease)
Abstract VisionMD, an open-source software for automated video-based analysis of MDS-UPDRS Part III motor tasks, offers precise, objective, and scalable assessments of motor symptoms in Parkinson’s disease and other movement disorders. Leveraging deep learning, VisionMD tracks body movements to compute kinematic features that quantify symptoms severity and supports longitudinal monitoring. VisionMD’s user-friendly, customizable framework empowers clinicians and researchers to objectively evaluate motor symptoms in persons with movement disorders without specialized hardware.